Perspectives on Continuing Education Programs for Foundation-Level Drugstore Pharmacists in Japan - Tomoko Terajima; Kumiko Matsushita; Seiichiro Yamada; Hiroaki Suzuki; Shingo Yano; Mizue Makimura; Shigeo Yamamura (Pharmacy, 2020)
Background: Continuing education (CE) is important for developing and updating pharmacists’ knowledge, skills, and attitudes. CE programs should be developed according to social requirements but also based on personal requirements depending on the sectors the pharmacists work in. This research aims to explore perspectives on CE programs for foundation-level drugstore pharmacists in Japan. Method: Foundation-level drugstore pharmacists were asked what CE programs or training they needed to develop patient care or customer satisfaction. Results: We obtained 417 opinions (multiple answers were allowed) in 280 responses from 460 pharmacists (male: 245 and female: 215). The products and goods about which drugstore pharmacists wanted to learn covered a wide range. They wanted to learn about taping skills, tests, and products and devices related to care of the elderly. Taping skill would be quite unique for drugstore pharmacists. For special populations, they wanted knowledge and skills related to pregnancy tests and the safe use of medication by pregnant or lactating women. Conclusion: Drugstore pharmacists in Japan have different CE and continuing professional development (CPD) requirements from community pharmacists. The benefits of CE programs meeting pharmacists’ requirements should be evaluated in future research.